Implikasi Dana Otsus dalam Mengurangi Kemiskinan di Papua: Dengan Error Correction Model (ECM) - Ullya Vidriza; Daniel Ananta Talmera (FISIP UWP, 2022)
Special Autonomy funds is a special revenue post for the implementation of special autonomy which amount is equivalent to 2% of the ceiling of National General Allocation Fund for 25 years, which is mainly intended for financing education and health. The distribution of special autonomy funds is expected to improve the community's economy in order to realize justice in the concept of regional product management, increase community welfare, and empower human resources. However, practically there are some discrepancies between the expectation and reality Ironically, amid the abundance of Papua Special Autonomy funds in the last two decades, poverty is still the main problem. This study aims to analyze the impact of special autonomy funds on poverty alleviation in Papua, with the assumption that the special autonomy funds are fully distributed using Error Correction Model Analysis. The results showed that the Special autonomy funds significantly reduce the Number of Poverty in short-run and long run.